Quantum Mechanics for Pedestrians 1 - Pade, Jochen (Springer, 2014)
The first edition of ‘Physics for Pedestrians’ was very well received. Repeatedly, I was asked to extend the considerations to relativistic phenomena. This has now been done in this second edition. Volume 1 contains elements of relativistic quantum mechanics, and Volume 2 contains elements of quantum field theory. These extensions are placed in the Appendix. They are not comprehensive and complete presentations of the topics, but rather concise accounts of some essential ideas of relativistic quantum physics. Furthermore, for the sake of completeness and to guarantee a consistent notation, there are outlines of relevant topics such as special relativity, classical field theory, and electrodynamics. In addition, a few minor bugs have been fixed and some information has been updated. I gratefully thank Svend-Age Biehs, Heinz Helmers, Stefanie Hoppe, Friedhelm Kuypers and Lutz Polley who have helped me in one way or another to prepare this second edition.
Fundamentals